2016
DOI: 10.1111/acer.13285
|View full text |Cite
|
Sign up to set email alerts
|

Drinking, Alcohol Use Disorder, and Treatment Access and Utilization Among U.S. Racial/Ethnic Groups

Abstract: Data from approximately 140 articles and reports published since 2000 on drinking, alcohol use disorder (AUD), correlates of drinking and AUD, and treatment needs, access and utilization were critically examined and summarized. Epidemiological evidence demonstrates alcohol-related disparities across U.S. racial/ethnic groups. American Indians/Alaska Natives generally drink more and are disproportionately affected by alcohol problems, having some of the highest rates for AUD. In contrast, Asian Americans are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(131 citation statements)
references
References 126 publications
(180 reference statements)
6
125
0
Order By: Relevance
“…Another limitation of prior literature on gender disparities is that there has been very little formal investigation of the factors driving gender disparities in alcohol services utilization, which is in stark contrast to the large and expanding literature on racial/ethnic alcohol disparities (Chartier and Caetano, ; Grant et al., ; Vaeth et al., ). To achieve equity in alcohol services utilization between women and men, we must have a thorough understanding of the determinants of gender disparities in use of such services.…”
Section: Studies On Gender Differences In Alcohol Services Utilizationmentioning
confidence: 99%
“…Another limitation of prior literature on gender disparities is that there has been very little formal investigation of the factors driving gender disparities in alcohol services utilization, which is in stark contrast to the large and expanding literature on racial/ethnic alcohol disparities (Chartier and Caetano, ; Grant et al., ; Vaeth et al., ). To achieve equity in alcohol services utilization between women and men, we must have a thorough understanding of the determinants of gender disparities in use of such services.…”
Section: Studies On Gender Differences In Alcohol Services Utilizationmentioning
confidence: 99%
“…Compared to non‐Hispanic Whites, Hispanic Americans showed lower prevalence rates of lifetime, past year, and past month alcohol use (Villalobos and Bridges, ). Hispanic adults had high estimates of binge drinking across national surveys, however (McKinney and Caetano, ; Vaeth et al., ). Data from the National Alcohol Surveys in 2005 and 2010 revealed that Hispanic Americans had similar composite scores for heavy drinking as White Americans, but Hispanic men reported higher rates of alcohol‐related problems associated with injuries, work, and legal consequences than their White counterparts (Witbrodt et al., ).…”
Section: Alcohol Use and Acculturation Among Hispanic Americansmentioning
confidence: 99%
“…A large body of research has examined acculturation as a determinant of alcohol use (Vaeth et al., ). Acculturation is the process of psychological, behavioral, sociocultural change, and adaptation that happens when intercultural contact occurs between individuals or among groups of people (Schwartz et al., ; Zamboanga et al., ).…”
Section: Alcohol Use and Acculturation Among Hispanic Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol dependence (AD) is a global problem that affects individuals from all racial/ethnic groups and all levels of socioeconomic standing. Previous studies suggest that there is considerable variation in patterns of drinking and alcohol use disorders across different US racial/ethnic groups (Caetano, Clark & Tam ; Chartier & Caetano ; Vaeth, Wang‐Schweig & Caetano ). For example, analysis of college‐aged students (i.e.…”
Section: Introductionmentioning
confidence: 99%